THE ROLE OF CULTURE IN SHAPING WOMEN’S ENTREPRENEURSHIP: EVIDENCE FROM SABAH, MALAYSIA - Salmah Topimin; Irma Wani Othman; Haslinda Hassan; Siti Nor Bayaah Ahmad (International Journal of Accounting, Finance and Business, 2021)
Women's social environments are shaped by various cultural elements that influencetheir behaviour and actions in the public sphere. As such, this paper explores how socioculturalelements in women's social environments influence their entrepreneurial activities. Indepthinterviews with ten women entrepreneurs in the West Coast of Sabah were conducted.Although some cultural factors appear to assist women in pursuing their entrepreneurialactivities, this study found that the factors also inhibit women entrepreneurs from realisingtheir full business potential. The findings reveal that socio-cultural factors influence thebusiness decisions made by women entrepreneurs. It becomes apparent that the concept ofgender appropriate behaviour has given impact on women’s businesses in several aspects:motivating factors, industry preferences and strong family commitment as well as patriarchalpressures on business. This paper concludes that socio-cultural factors are critical tounderstanding of women’s entrepreneurship, thus, adding to the body of knowledge about theimpact of culture on women's entrepreneurship.